A new stepped-channel liquid cooling plate thermal management system combined with composite phase change materials. (5th July 2022) - Zhang, Furen; Gou, Huan; Xie, Chenchuang; He, Yanxiao; Zhu, Yilin; Lu, Fu; Liang, Beibei; Xiao, Kang
Highlights: A novel stepped structure channel combining parallel and tree channel was proposed. Effects of structure style, number, structural parameters were analyzed. Filling CPCM to enhance cooling performance and reduce the weight of cooling plate. Average temperature and pressure drop were reduced by 2.46 °C and 22.14 Pa. Abstract: Aiming at the problems of large temperature gradient of traditional parallel channel and high pressure loss of tree fractal channel, a novel stepped liquid cooling plate combining the above two structures was proposed in this paper. Firstly, based on the liquid cooling plate experimental platform, the reliability of computational fluid dynamics method was verified by experiments. Secondly, based on computational fluid dynamics and orthogonal test methods, the effects of the arrangement form of cooling channels, the number of inlets and outlets and structural parameters (number of channels, longitudinal length, width, thickness and width of inlets and outlets) were analyzed. In comparison with the original model, the average temperature and pressure drop were reduced by 1.17 °C and 22.14 Pa, respectively. Finally, in order to further improve the heat dissipation effect of the system, a new hybrid liquid cooling plates formed by filling the liquid cooling plate with composite phase change material were proposed. The results indicated that the cooling performance of the hybrid liquid cooling plate filling with more phase change material was better, meanwhile, the average temperature and pressure drop were reduced by 2.46 °C and 22.14 Pa, respectively, compared with the original model. In addition, the effect of inlet mass flow was discussed. The results revealed that the cooling performance of hybrid liquid cooling plate was better at lower mass flow rate, while the cooling performance of the liquid cooling plate was better at higher mass flow rate.